Indicators of knowledge, usefulness, and use of ICT among primary schoolteachers - Maria T. Sanz; Carmen Melgarejo; Emilia López-Iñesta (OmniaScience, 2023)
This paper presents a study on the perceptions of primary school teachers regarding their knowledge, usefulness, and use of Information and Communication Technologies (ICT) in education. Likewise, the relationship between sex, age, working time and the educational center in which it is found with the perceptions about ICT is obtained. To answer these questions, a battery of 14 categorical closed questions is designed, divided into four blocks: socio-demographic information; knowledge of ICT; usefulness of ICT; and use of ICT. In the context of measuring the knowledge, usefulness and use of ICT in education, the novelty of this work relies on the design of an indicator for each of the ICT-related blocks following the methodology of Human Development Indicators created by the United Nations Development Program. In this research, 119 teachers from Spanish primary schools were chosen as the study sample to answer the questions' battery. The results show a direct relationship between knowledge, usefulness, and use, although not significant. Although teachers are aware of the usefulness of ICT, and the Covid-19 pandemic has increased the use of technological tools for planning teaching in blended or distance learning lessons, this does not mean teachers have a greater knowledge of ICT. In addition, the findings indicate a greater knowledge by teachers in public schools, which contrasts with the finding that teachers in grant-assisted schools make the most use of ICT and find it the most useful. Finally, it is also suggested that the study's methodology and approach could be applied to other contexts or countries.